Fuzzy-CAC for LSP Setup in GMPLS Networks - Jeļinskis, J.; Rutka, G.; Lauks, G. (Elektronika ir Elektrotechnika, 2010)
In this investigation the new Fuzzy-CAC algorithm is proposed for RSVP-TE protocol development for use in GMPLS networks. The Fuzzy-CAC algorithm is based on expert knowledge IF-THEN rule collection. Decision making is flexible, due to the contemporaneous analysis of input variables and lack of crisp valued inputs. Classical threshold CAC algorithm is compared to the Fuzzy algorithm implementation, main characteristics are analyzed. Experimental data are depicted and future research subjects are described.